Optic neuritis caused by canine distemper virus in a Jack Russell terrier - Richards, Tara R. (Canadian Veterinary Medical Association, 2011)
An atypical case of canine distemper (CD) was diagnosed in a vaccinated healthy adult dog. The patient was presented circling, seizuring, and blind. Postmortem examination resulted in a diagnosis of CD. Optic neuritis was diagnosed, a finding not previously described in the context of CD virus infection presenting solely with neurological signs.